Level of purposeful hand function as a marker of clinical severity in Rett syndrome - Downs, J.; Bebbington, A.; Jacoby, P.; Williams, A.; Ghosh, Soumya; Kaufmann, W.; Leonard, H. (Wiley-Blackwell Publishing Ltd., 2010)
Aim - We investigated relationships between hand function and genotype and aspects of phenotype in Rett syndrome. Method - Video assessment in naturalistic settings was supplemented by parent-reported data in a cross-sectional study of 144 females with a mean age of 14 years 10 months (SD 7y 10mo; range 2y–31y 10mo), 110 of whom had a mutation of the methyl CpG binding protein 2 (MECP2) gene. Ordinal logistic regression was used to assess relationships between hand function and MECP2 mutation, age, a modified Kerr score, Functional Independence Measure for Children (WeeFIM), ambulation level, and frequency of hand stereotypies. Results - Approximately two-thirds of participants demonstrated purposeful hand function, ranging from simple grasping skills to picking up and manipulating small objects. In participants with a confirmed MECP2 mutation, those with the p.R168X mutation had the poorest hand function on multivariate analysis with C-terminal deletion as the baseline (odds ratio [OR] 0.19; 95% confidence interval [CI] 0.04–0.95), whereas those with the p.R133C or p.R294X mutation had better hand function. Participants aged 19 years or older had lower hand function than those aged less than 8 years (OR 0.36; 95% CI 0.14–0.92). Factors that were associated with better hand function were lower Kerr scores for a 1-point increase in score (OR 0.77; 95% CI 0.69–0.86), higher WeeFIM scores for a 1-point increase in score (OR 1.08; 95% CI 1.04–1.12), and greater ambulation than those completely dependent on carers for mobility (OR 22.64; 95% CI 7.02–73.08). The results for participants with a confirmed pathogenic mutation were similar to results obtained when participants without a mutation were also included. Interpretation - Our novel assessment of hand function in Rett syndrome correlated well with known profiles of common MECP2 mutations and overall clinical severity. This promising assessment could measure clinical responses to therapy.